Squamous cell carcinoma of the eyelid masquerading as 'malignant' ophthalmopathy of Graves's disease. - Ford, H C (1983)
A patient with Graves's disease is described in whom the periorbital changes of severe ophthalmopathy and iatrogenic Cushing's syndrome delayed the diagnosis of a squamous cell carcinoma of the eyelid. It is suggested that the immunosuppressive therapy which the patient received may have enhanced the growth of a pre-existing malignancy.